Analisis soal matematika tipe higher order thingking skill (hots) kelas vii mts pondok pesantren khairul fatihin nw ijobalit - Febian Asri; Baidowi Baidowi; Dwi Novitasari; Muhammad Turmuzi (Griya Journal of Mathematics Education and Application, 2022)
This study aims to describe the quality of the analysis of Class VII mathematics problems of MTs Khairul Fatihin NW Ijobalit academic year 2020/2021 HOTS type viewed from the aspects of validity, reliability, difficulty level, differentiator and finisher. The type of research used is quantitative descriptip. Subjects in this study were students of Class VII MTs Pondok Pesantren Khairul Fatihin NW Ijobalit which amounted to 37 people. The object of the study was hots type math problems and the answers of grade VII students of the even Semester of the 2020/2021 school year, which consisted of 35 objective questions. Data collection techniques are carried out by interview and documentation methods. The results showed that: there are 4 questions category HOTS where all the questions cognitive level is C4 in terms of validity, item hots problem classified as a valid problem; in terms of reliability, hots problem classified as a matter of moderate reliability with an index of 0.469; in terms of differentiating power, the item about HOTS is in the category enough with a percentage of 75%; in terms of difficulty level, the item about hots classified as having a moderate difficulty level; in terms of the effectiveness of the Spieler, hots problem has a very good Spieler effectiveness because the Spieler is selected with a percentage of more than 5%.